Novel biomarkers predict ablation outcomes in long stranding persistent atrial fibrillation. (19th May 2022) - Boyalla, V; Bodinier, B; Kralj-Hans, I; Haldar, S; Khan, HR; Shi, R; Cantor, E; Hussain, W; Jones, DG; Jarman, JWE; Markides, V; Chadeau-Hyam, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): NIHR Background: Ablation of long-standing persistent atrial fibrillation (LSPAF) is not always successful. The arrhythmia burden was reduced by 75% by 12 months in majority (72%) of patients with LSPAF who underwent surgical or percutaneous ablation in the CASA-AF trial. We hypothesised that biomarker(s) improve prediction of clinical success and offer insights into mechanisms. Objective: To identify biomarkers that predict success (75% arrhythmia burden reduction) after ablation for LSPAF at 12-months. Methods: Amongst patients participating in the CASA-AF RCT (ISRCTN18250790), pre-ablation serum samples were selected for 20 patients who met criteria for ablation-success at 12 months, and 20 who did not. Olink ProteomicsTM (Sweden) provided analyses using three biomarker panels [inflammation (INFL), cardiovascular III (CVD III), and cell cytology (CELL)] each containing 92 biomarkers. Univariate and multivariable analyses were adjusted for age, sex, BMI, LA diameter and CRP. ROC analysis was undertaken to assess the diagnostic accuracy of the biomarkers. To counter the false discovery rate, Benjamini-Hochberg correction was utilised. Results: When patients with ablation-success and -failure were compared, no differences in demographics or cardiac function were found. On univariate analysis, several biomarkers in each panel were associated with ablation-success. Multivariable analysis narrowed the range of biomarkers and identified those that were jointly predictive of outcome: INFL (MCP1 + CD8A + CD40, Figure 1), CVD III (FAS + CPB1) and CELL (GCG + ENTPD6 + IL17RB). These joint biomarkers were analysed using ROC (Figure 2), which showed that increases of biomarkers on the INFL panel (MCP1 + CD8A + CD40) were associated with a greater risk of failure and achieved the highest AUC for prediction of outcome [0.82 (0.75-0.87)]. Conclusion: The increase in the serum concentration of markers of inflammation (MCP1 + CD8A + CD40) might be used to identify patients less likely to have sustained benefit from LSPAF ablation. Further studies are required to confirm their prognostic value as pre-procedural biomarkers.